FUNCTIONS OF HUMOR IN CLASSIC ARABIC LITERATURE - Nurbaidah, Siti; Wijana, I Dewa Putu (Lugatuna : Jurnal Prodi PBA, 2023)
This article discusses the function of verbal humor in classic Arabic literature. The goals of this research are first, identifies and explain the humor function applied in classic Arabic literature in creating humor situation. The source of data in this study is taken from a book entitled “Mi’ah Nuktoh wa Nuktoh” created by Marwah Imadudin. The qualitative and quantitative method was implied. As a result, the humor function applied in classic Arabic literature were classified under the three classifications of solidarity, power and psychological functions. Based on three categories of humor, it is found: (1) Solidarity function 41 humor with (40,59%), (2) Power function 19 humor with (18,81%), and (3) Psychological function 41 (40,59%). The highest frequency of function of humor is solidarity and psychological function. Both functions have the same amount of data and the same percentage of the total 101 data. Thus, it can be concluded that the function of humor in the study of classical Arabic literature tends to utilize the functions of solidarity and psychology.